Suitability of Nasal and Deep Nasopharyngeal Swab Sampling of Calves in the Mycoplasma bovis Control Program - Pohjanvirta, Tarja; Vähänikkilä, Nella; Talvitie, Vera; Pelkonen, Sinikka; Autio, Tiina (Frontiers in Veterinary Science, 2021)
Mycoplasma bovis (M. bovis) is an important cattle pathogen affecting animal health, welfare, and productivity. The main disease syndromes are mastitis, pneumonia, and otitis media in young stock, as well as arthritis. Response to antibiotic treatment is poor and no effective vaccine is available. Asymptomatic carriers are common and usually harbor the organism in the airways or mammary glands. Purchase of carrier animals is a major risk for the introduction of infection into naive herds. Following the detection of M. bovis in Finland in 2012, a voluntary control program was established. It aims to prevent the spread of the infection and to help farms attain certification of a low M. bovis risk. Among the diagnostic tools in the program, nasal swabs (NS) from young calves have been tested for M. bovis to indicate the infection status of the herd. In this study, we assessed the suitability of this test method. We analyzed the effectiveness of NS and deep nasopharyngeal swabs (NP) to detect M. bovis in pneumonic and healthy calves in dairy herds recently infected with M. bovis. In pneumonic calves, NP sampling followed by culture and real-time PCR demonstrated a proportion of positive agreement (PPA) of 0.91 compared to bronchoalveolar lavage (BAL), whereas NS showed only 0.5 PPA compared to BAL. Among healthy dairy calves, overall M. bovis prevalence in NS was 29.6%. The highest rate of shedding (43%) occurred in calves 31 to 60 days old. At the calf level, M. bovis prevalence in NP samples was 47% compared to 33% in NS samples among the 284 studied calves. However, at the herd level, NS sampling classified 51 out of 54 herds with a positive infection status as infected, whereas in NP sampling, the respective figure was 43 out of 54 herds (p = 0.061). In conclusion, NS sampling from calves under six months of age and analyzed by real-time PCR is a cost-efficient method for a control program to detect M. bovis in dairy herds, even if no M. bovis mastitis has been detected in the herd. For pneumonic calves, we recommend only NP or BAL sampling.